THE ROLE OF JOB SATISFACTION IN MEDIATING THE EFFECT OF WORKLOAD AND COMPETENCE ON EMPLOYEE PERFORMANCE AT PT PLN (PERSERO) UP2B NTB - Putu Yudiadi Pranata; Trianasari; Komang Krisna Heryanda (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The purpose of this study was to analyze the effect of workload and competence on employee performance with job satisfaction as a mediating variable at PT PLN (Persero) UP2B NTB. The research method used was quantitative with a census approach, involving the entire employee population of 54 people. Data were collected through a Likert scale questionnaire and analyzed using Structural Equation Modeling - Partial Least Square (SEM-PLS) with the help of SmartPLS software . The results of the study showed that: (1) workload did not have a significant effect on employee performance; (2) competence had a positive and significant effect on employee performance; (3) workload did not have a significant effect on job satisfaction; (4) competence had a positive and significant effect on job satisfaction; (5) job satisfaction had a positive and significant effect on employee performance; (6) job satisfaction did not mediate the relationship between workload and employee performance; (7) job satisfaction partially mediated the relationship between competence and employee performance. The R-square value for job satisfaction was 72.5% and employee performance was 84.1%, with a Goodness of Fit value of 0.770 (high category).